2015
DOI: 10.1002/spe.2312
|View full text |Cite
|
Sign up to set email alerts
|

Selecting a software engineering tool: lessons learnt from mutation analysis

Abstract: International audienceSoftware developers employ many tools in every step of the development. As automation progresses, tools take a more and more important place. A common and difficult problem is choosing a tool among every tool for a given task.As a particular instance of this problem, this paper considers mutation analysis tools. Mutation analysis is a way to evaluate the quality of a test suite. The quality is measured as the ability of the test suite to detect faults injected into the program under tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Among these tools, Proteum/IM 2.0 [38] and MILU [39] are the most widely used in other research studies, such as to evaluate selective mutation [14] or higher order mutation [12]. While MILU offers fewer features than Proteum, it automates most of the mutation analysis process, in contrast to Proteum which requires considerable manual intervention [40].…”
Section: F Mutation Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these tools, Proteum/IM 2.0 [38] and MILU [39] are the most widely used in other research studies, such as to evaluate selective mutation [14] or higher order mutation [12]. While MILU offers fewer features than Proteum, it automates most of the mutation analysis process, in contrast to Proteum which requires considerable manual intervention [40].…”
Section: F Mutation Toolmentioning
confidence: 99%
“…The survey by Delahaye and du Bousquet [40] states that MILU implements the 77 mutation operators that Agrawal et al [17] identified for C. However, the number of mutation operators has been reduced in MILU 3.2 -following studies on SM [13], [14], only 12 of those 77 operators were included in this version. Two additional operators are also included: SSDL (delete statements) and SBRC (replaces break by continue).…”
Section: G Cost Reduction Techniquesmentioning
confidence: 99%
“…Among the Java tools, the most popular ones are the MuJava [7] and the Major [5]. Unfortunately, these tools were built to support research projects and thus, their practical use is limited [3]. In short PIT offers the following three major advantages over the other tools: a) it is open source, b) it is well integrated with development tools, as it offers a Maven plugin and c) it is quite robust and actively maintained.…”
Section: Mutation Testingmentioning
confidence: 99%
“…PIT also operates on the latest version of Java. For further details regarding the tool please refer to the work of Delahaye et al who compared the existing Java mutation testing tools [3].…”
Section: Mutation Testingmentioning
confidence: 99%
See 1 more Smart Citation